2006
DOI: 10.3892/or.15.3.545
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in novel candidate tumor suppressor genes, ING1 and ING2 in human lung cancer

Abstract: The ING1 gene is involved in the regulation of the cell cycle, senescence, and apoptosis and is a novel candidate tumor suppressor gene. ING2, another gene in the ING family, was identified and cloned. The functions of ING1 and ING2 largely depend on the activity of p53. To determine whether an alteration in these genes plays a role in carcinogenesis and tumor progression in lung cancer, we screened 30 human lung cancer cell lines and 31 primary lung cancer tumors for mutations in these genes using polymerase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 24 publications
3
37
0
Order By: Relevance
“…ING1 downregulation was observed in different tumor types (breast, gastric, esophageal, blood, lung and brain) (Gong et al, 2005), whereas protein mislocalization was described in tumors of different origin (Nouman et al, 2002). ING2 expression was reduced in colorectal, hepatocellular carcinoma, prostate, pancreatic, lung cancer and cutaneous melanoma (Nagashima et al, 2001;Lu et al, 2006;Okano et al, 2006). Allelic loss and reduced expression of ING3 have been also reported (Gunduz et al, 2002;Nagashima et al, 2003).…”
Section: Introductionmentioning
confidence: 86%
“…ING1 downregulation was observed in different tumor types (breast, gastric, esophageal, blood, lung and brain) (Gong et al, 2005), whereas protein mislocalization was described in tumors of different origin (Nouman et al, 2002). ING2 expression was reduced in colorectal, hepatocellular carcinoma, prostate, pancreatic, lung cancer and cutaneous melanoma (Nagashima et al, 2001;Lu et al, 2006;Okano et al, 2006). Allelic loss and reduced expression of ING3 have been also reported (Gunduz et al, 2002;Nagashima et al, 2003).…”
Section: Introductionmentioning
confidence: 86%
“…Using the tissue microarray technology and immunohistochemistry, we for the first time demonstrated that ING2 nuclear expression is reduced in human melanomas compared to dysplastic nevi ( There is only one recent report by Okano et al (2006) showing that ING2 expression is reduced in six of seven lung cancer cell lines. However, these authors did not detect any ING2 mutation in 31 human lung cancer cell lines and 30 lung cancer biopsies.…”
Section: Discussionmentioning
confidence: 99%
“…Recently reduced expression of ING2 mRNA as well as protein was observed in hepatocellular carcinoma (HCC) [95]. Decreased ING2 expression (but not ING2 mutation) has been observed in lung cancer [96]. Decrease of nuclear ING2 protein was observed in melanoma [57].…”
Section: Disorders Of Ing Family Genes In Human Tumorsmentioning
confidence: 96%